Foot Reflexology Massage for Managing Diabetic Peripheral Neuropathy Symptoms in a Patient with Type 2 Diabetes Mellitus: Case Study - Malik Zainal; Zaqqi Ubaidillah (Jurnal Kesehatan dan Kedokteran, 2026)
Diabetic Peripheral Neuropathy (DPN) is a common complication of Type 2 Diabetes Mellitus, often causing numbness, tingling, nocturnal cramps, and sleep disturbance. Complementary nursing interventions are needed to support symptom management in primary healthcare settings. Objective: This study aimed to describe the implementation of foot reflexology massage and its potential contribution to reducing peripheral neuropathy symptoms in a patient with Type 2 Diabetes Mellitus. Method: This study used a descriptive case study design with an Evidence-Based Practice Nursing approach. The subject was a 58-year-old female patient with Type 2 Diabetes Mellitus and peripheral neuropathy symptoms. Data were collected through nursing assessment, physical examination, Toronto Clinical Neuropathy Score (TCNS), and Ankle Brachial Index (ABI). Foot reflexology massage was administered three times per week for two weeks, totaling six sessions. Data were analyzed descriptively by comparing pre- and post-intervention findings. Findings: Before the intervention, the patient had moderate neuropathy with a TCNS score of 10, an ABI value of 0.91, cold acral temperature, dry foot skin, and persistent numbness and tingling. After six sessions, the TCNS score decreased to 7, indicating mild neuropathy, while the ABI increased to 0.96. The patient also reported reduced tingling, disappearance of nocturnal cramps, warmer feet, improved skin moisture, and better sleep quality. Implications: Foot reflexology massage may serve as a simple, low-cost, non-invasive complementary nursing intervention for managing DPN symptoms in primary healthcare. Originality/Value: This study provides a clinical description integrating TCNS and ABI assessment within an Evidence-Based Practice Nursing framework.